Corporate social responsibility: strategic directions for the evolution of development companies - Loktionova, Y.; Beseda, Maksym; Sharshun, Philipp (Ways to Improve Construction Efficiency, 2024)
In the course of writing this article, the author defines the role of corporate social responsibility (CSR) in the formation of strategic management of development companies. The study includes an analysis of the essence of CSR as a key element of modern business management, which implies that businesses recognize their responsibility to society and the environment. The impact of CSR on long-term economic stability, environmental sustainability and social responsibility is analyzed. Analysis of the strategic directions of development of development companies based on CSR allows us to identify the key elements of integrating ethical standards into corporate strategy, including transparency and accountability in all aspects of business, development of responsible partnerships with suppliers and investors, and introduction of innovations. The innovation aspect includes the digitalization of construction processes, the use of the latest materials and methods, and investments in research that improve the quality of construction and reduce the negative impact on the environment. The article summarizes the results of the study, which show that the strategic implementation of CSR principles not only improves the reputation of development companies and strengthens their competitive position in the market, but also contributes to long-term economic growth, reduction of operating costs and increase in profitability. The author emphasizes the importance of integrating CSR into the activities of development companies to ensure sustainable development in the real estate sector. In particular, the study shows that the effective implementation of CSR practices, including economic benefits, environmental sustainability, social development and ethical corporate governance, opens up new opportunities for growth and development in the development sector, adaptation to modern challenges and strengthening their market position.